Problema corporalităţii în proza lui Max Blecher şi a lui Bruno Schulz din perspectiva antropologiei filosofice - Teodorowicz, Justyna (Studia Romanica Posnaniensia, 2020)
The article discusses the problem of corporality in Max Blecher’s novels and Bruno Schulz’s short stories from the perspective of philosophical anthropology. The motifs of body and matter, predominant in both authors’ work, are a means of presenting the place of man in the universe and dealing with such questions as identity or ontology. Through the use of somatic metaphors all the elements of the fictional world are anthropomorphised or given human characteristics, which leads to the lack of hierarchy. Whereas philosophical anthropology presents humans as active and rational beings, Blecher and Schulz stress the illusion of man’s individuality and question his privileged position in the world.